PENGARUH LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN UMKM DI KECAMATAN TEJAKULA - I Made Santiara; Ni Kadek Sinarwati (CAPITAL: Jurnal Ekonomi dan Manajemen, 2023)
Financial literacy helps a person in managing his finances and in making important decisions regarding the investments he makes. Having good financial literacy can enable individuals to make informed decisions about their money and minimize the possibility of having financial problems. This study aims to determine the influence of financial literacy on the financial management of MSMEs in Tejakula. This research uses an associative approach. The sample from this study was 50 MSME actors in Tejakula. The data used in this study is primary data. The data collection technique in this study was questionnaire. The data analysis technique used in this study is simple regression analysis. The results of this study show that financial literacy has a positive and significant effect on financial management.